Analisis Pertumbuhan Ekonomi Provinsi Jawa Timur Beserta Faktor-Faktornya Menggunakan Model Robust Geographically Weighted Regression-Pendugaan M - Halimah Nur Mushaharah; Rosita Kusumawati; Bayutama Isnaini (Indonesian Journal of Applied Statistics, 2025)
Economic growth is a successfull benchmark of nation-building and plays a role in a nation’ welfare. Economic growth in districts/cities measured by gross regional domestic product at constant prices (GRDP constant prices). East Java is the second province after DKI Jakarta as the biggest contributor to the Indonesian economy in 2022 with  economic growth rate values calculated by GRDP constant prices. However, East Java’s economic growth has gaps. As 23 of 38 districts/cities in East Java have economic growth values lower than national economic growth. Glaring gaps could be identified as an outlier and it could happen by many factors. This study aims to model economic growth and its factors with a robust analysis model against an outlier called robust geographically weighted regression-M estimation (RGWR-M). This study used secondary data from BPS Provinsi Jawa Timur and KEMENKEU’s SIKD data portal namely HDI, public health center, population density, economic activity, capital expenditure, and GRDP constant prices in East Java Province in 2022. The result showed that RGWR-M is the best model when an outlier is detected compared to OLS and GWR in analyzing factors that are suspected to affect economic growth in East Java Province in 2022 with  MAD’s values. RGWR-M model produces six mapping groups of significantly influential variables and one group of uninfluential variables. The groups formed to have different parameter estimation results in each district/cities.Keywords: GRDP constant prices; outlier; RGWR-M.